LA GUERRA COMO CUESTIÓN SOCIAL: UN ACERCAMIENTO A LA POLÍTICA SOCIAL COLOMBIANA - Castaño Zapata, Daniel (Universidad de Costa Rica, 2013)
The aim of this article is to make some lines raised to think the relationship between social policy in Colombia and internal war, which takes place in this country since the middle of XX’s Century. For this study, it makes a presentation from the conceptual approach proposed to be the main dimensions, theoretical and empirical, that Colombian social policies are built by war.